DAMPAK LIBERALISASI PERDAGANGAN DUNIA TERHADAP PERMINTAAN DAN PENAWARAN KOPI INDONESIA - Abdul Hakim; Yuli Haryati (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2008)
Indonesia is one of exporting country coffee in the world. World Trade Liberalization wants an abolition of all kind of trade resistance that is: tariff, quota and subsidy. This Research bent on to know: (1) factors that influence supply and demand coffee Indonesia, (2) analysis of condition supply and demand coffee Indonesia when agreement applying IMF, AFTA, and WTO.  Research Result indicates that: (1) Supply coffee Indonesia is formed from amount of production coffee Indonesia is added amount stock coffee Indonesia is added import coffee Indonesia less the amount of  exporting coffee Indonesia, whereas (2) demand coffee Indonesia is influenced by price coffee Arabica  Indonesia, amount Import coffee Indonesia, resident population Indonesia and sugar price in Indonesia. Today government Indonesia have not yet when its to apply policy of import tariff 0 % base rule WTO, until ideal policy alternative was for condition of coffee Indonesia today is : Government Policy by applying import tariff 1,05%, fee improvement as high as 10% and degradation of manure price as high as 10% at this condition will cause improvement at supply coffee Indonesia from 503.360 tons become 520.620 level tons as high as 20.260 tons (4,05%), level demand from 175.000 become 175.503 level tons as high as 503 tons (0,29%). Improvement also happened in exports from 329.062 tons become 349.237 ton or levels as high as 20.175 tons (6,13%) whereas to import not too high its improvement that is from 3.197 tons become 3.492 ton or levels as high as 295 tons (9,22%). Key word : Liberalization trading, Supply and demand, Coffee.